Cover to cover : - Day, Richard R. (Oxford University Press, 2007)
Cover to Cover is a three-level series that combines reading comprehension and vocabulary skills with extensive reading. The reading passages, from magazines, newspapers, and classics provide a practical way to combine intensive and extensive reading seamlessly.